High preterm birth at Cipto Mangunkusumo Hospital as a national referral hospital in Indonesia (Medical Journal of Indonesia, 2017)
Background: Preterm birth is the leading direct that causes neonatal death. Indonesia was listed as one of the countries with the greatest number of preterm birth in 2010. This study aims to identify the prevalence and the potential risk factors of preterm birth among women underwent delivery in Cipto Mangunkusumo Hospital, an Indonesian national reference hospital. Methods: This retrospective cohort study involved 2,612 women who delivered between January and December 2013. Any clinical data which related to the potential risk factors and outcomes were recorded. The data were managed using chi-square for bivariate analysis and t-test or Mann-Whitney for numerical data followed by multiple logistic regression for multivariate analysis in SPSS version 20.0. Results: Preterm birth affected 1,020 of 2,616 pregnancies (38.5%). Non-booked patients increased nearly twice risk for preterm delivery (OR 1.89, 95% CI 1.37-2.61). While women with singleton pregnancy (OR 0.17, 95% CI 0.12-0.25), head presentation (OR 0.75, 95% CI 0.63-0.89), and regular ANC (OR 0.67, 95% CI 0.54-0.84) had lower risk for preterm birth. Apgar score, birthweight, and mode of delivery were significantly different between the pre-term group and the full-term group. Conclusion: Prevalence of preterm birth in Cipto Mangunkusumo Hospital was approximately 2.5 times higher compared to the national number. Several factors reducing preterm birth rate include singleton pregnancy, head presentation, and regular ANC.